The effectiveness of social-themed picture book reading in promoting children’s prosocial behavior - Chen, Honglin; Lyu, Dannuo; Zhu, Liqi (Frontiers in Psychology, 2025)
IntroductionThere is a need for an effective and low-cost approach to promote prosocial behavior in preschool children. This study examines the effectiveness of parent-child shared reading of socially themed picture books on prosocial behavior in preschoolers, and explores the mediating role of empathy.MethodsSixty children (aged 4-5 years) and their parents were randomly assigned to either the intervention group, which read socially themed picture books, or the control group, which read books on other topics. Shared reading sessions took place twice a week for eight weeks. Prosocial behavior tasks and the Empathy Questionnaire (EmQue) were administered pre- and post-intervention.ResultsChildren in the intervention group scored significantly higher on prosocial behavior and empathy than those in the control group. Mediation analysis further revealed that empathy fully mediated the relationship between shared reading of socially themed picture books and prosocial behavior.DiscussionThese findings highlight the role of empathy as a key mechanism through which socially themed picture books promote prosocial behavior. This research provides valuable insights for family education, highlighting a low-cost approach that promotes children’s social development through everyday storytelling without the need for specialized training.